ANALISIS POSITIONING PRODUK KOPI INSTAN BERDASARKAN PERSEPSI MAHASISWA PONTIANAK DENGAN METODE MULTI DIMENSIONAL SCALING - Heruwansah, Heruwansah; Hillary, Janne; Ichsan, Ichsan (Institute of Computer Science (IOCS), 2024)
Multidimensional Scaling (MDS) is a procedure used to map respondents' perceptions or preferences, often utilizing two-dimensional visuals. The significance of MDS analysis lies in its ability to reveal the proximities between various products, which can serve as a foundation for determining the best strategies for market survival. In this study, the proximities of four instant coffee brands (Kopi Gadjah, Kopi Kapten, Kopi Neo, Kopi Obor) were analyzed. The objectives of this study were: 1) To determine the positioning or competitive market position among the four instant coffee products based on students' perceptions when considering a purchase of instant coffee, and 2) To identify the most superior instant coffee among the four according to student perceptions. This research used a survey method and was analyzed quantitatively. The sampling was carried out using the purposive sampling method, with 42 students from the State Polytechnic of Pontianak as the sample. The MDS method was employed to determine the position of each instant coffee brand. The results of the MDS an alysis indicated that the distance between Kopi Kapten and Kopi Obor was close, assuming that respondents perceived these two brands to have many similarities. If the proximity of the instant coffee brands reflects the level of competition, Kopi Kapten and Kopi Obor exhibited a high level of competition. In contrast, Kopi Gadjah and Kopi Neo did not directly compete with Kopi Kapten or Kopi Obor. Based on proximity to product attributes, Kopi Gadjah was identified as the most superior instant coffee among the four brands.